Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Wu, Yao; Li, Ting-Yong; Li, Jun-Yun; Cheng, Hai; Ning, You-Feng; Shen, Chuan-Chou; Yang, Yan; Zhao, Jing-Yao; Chen, Chao-Jun; Liang, Ming-Qiang; Xiao, Si-Ya; Qiu, Hai-Ying; et al. (Quaternary science reviews, 2023)
The iceberg melting-induced Heinrich events (HEs), which were first reported in 1988, caused a series of centennial-millennial global climate changes during the last glacial period. The patterns and details of low-latitude monsoons, oceans, and atmospheric circulation responses to HEs still need to be understood. Here, we report 11a resolved δ13C, δ18O and 36a resolved Mg/Ca, Sr/Ca and Ba/Ca multi-proxy stalagmite records during 42.29-37.14 ka BP from Yangkou cave, southwestern China. The Greenland ice cores and the δ18O of stalagmites from northern China recorded a rapid onset/termination of Heinrich stadials (HS) 4 (∼0.2 ka). However, the transition interval for the weakening/strengthening of the Asian summer monsoon (ASM) during HS4, as recorded by the southern Chinese stalagmite δ18O, is about 0.5 ka. Low latitude monsoons and hydrological variations are influenced by tropical oceans and interhemispheric thermal contrasts, which prolong the onset/termination transition process of HS4. Our findings highlight the importance of atmosphere-ocean interactions at low latitudes and in the Southern Hemisphere for ASM dynamics, which triggered the termination of millennial-scales abrupt climate events. During HS4, variations of the δ13C and trace elements ratios are inconsistent with δ18O, indicating that while the ASM is weakened, regional hydroclimate and local ecology are not significantly degraded, resulting in a relatively moderate hydrological environment. Prolonged southerly subtropical westerlies, super El Niño Southern Oscillation, western China autumn rains, and lower regional evaporation, may increase regional precipitation in different seasons and regulate hydrological conditions during HS4. As a result, while the ASM has weakened, regional hydrological conditions in the Yangtze River basin in southwest China maintain wet environmental conditions. The gradual northward shift of the Intertropical Convergence Zone and subtropical westerlies during the latter phase of HS4 will cause a limited northward shift of the rainfall bands. Although regional hydrological conditions deteriorate slightly in comparison to the early phase, it remains humid overall. We present new evidence that local hydrological conditions and ASM intensity were not fully coupled during the abrupt climate events on millennial scales in the last glacial period.